2021
DOI: 10.1016/j.heliyon.2021.e06636
|View full text |Cite
|
Sign up to set email alerts
|

Conservation agriculture-related practices contribute to maize (Zea mays L.) yield and soil improvement in Central Malawi

Abstract: Conservation agriculture-related practices (CARP) improve soil fertility, maize yield, and profitability. A study was conducted to generate evidence on the benefits of CARP in the long-term (nine years) in Salima District, Central Malawi. The objectives of the study were 1) to compare the maize yields between farmer practice and CARP interventions in the long-term, 2) to compare soil fertility changes between farmer practice and CARP interventions in the long-term, and 3) to verify the intercropping efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
3
5
0
Order By: Relevance
“…Related studies conducted in Western Kenya revealed that intercropping maize with crotalaria, groundnut and green gram showed significant economic benefits because all farming systems improved land productivity, household food and income security over the maize mono crop [18]. The study agrees with related studies conducted in Malawi which revealed that intercropping maize with groundnuts improved soil nutrients, maximized the use of environmental resources, resulting in increased maize productivity [19]. Similarly, studies conducted in Ethiopia, pointed out that intercropping of maize with different crops including soybean and desmodium resulted in reduced termite damage to maize and increased maize yield for the improved farmers' livelihoods [20].…”
Section: Discussionsupporting
confidence: 85%
“…Related studies conducted in Western Kenya revealed that intercropping maize with crotalaria, groundnut and green gram showed significant economic benefits because all farming systems improved land productivity, household food and income security over the maize mono crop [18]. The study agrees with related studies conducted in Malawi which revealed that intercropping maize with groundnuts improved soil nutrients, maximized the use of environmental resources, resulting in increased maize productivity [19]. Similarly, studies conducted in Ethiopia, pointed out that intercropping of maize with different crops including soybean and desmodium resulted in reduced termite damage to maize and increased maize yield for the improved farmers' livelihoods [20].…”
Section: Discussionsupporting
confidence: 85%
“…The increase in yields later in the trial period was due to increased soil organic matter, hence increased water retention 46 . In their study, Nyirenda and Balaka 47 found that under conservation agriculture-related practices, including intercropping maize with legumes, mulching, and reduced soil disturbance, increased biological activities on litter/residue, resulting in high production and stability in soil organic carbon and organic matter. Consequently, they observed increased maize yield under conservation agriculture compared to conventional practices.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Smale and Mason (2014) found that smallholder farmers adopted practices that are physically easy to use. Other practices such as mulching (Mutsamba et al, 2020;Nyirenda and Balaka, 2021), crop rotation (Gashure and Wana, 2022), and crop diversification (Beshir et al, 2022) are easy to practice and, as such, showed a high level of CSA practiced (Figure 3A). Perhaps one other common feature among these practices is that they have low capital and labor requirements, which is an advantage to smallholder farmers that do not have enough financial resources to adopt expensive practices.…”
Section: Climate-smart Agriculture Practices Identified In the Litera...mentioning
confidence: 99%